Effectiveness of Video Assisted Teaching Program on Knowledge Regarding Prevention and Management of Laryngitis among Primary School Teachers of Selected Primary Schools at Hassan - B., Mamatha; S., Damayanthi (Journal of Health and Allied Sciences NU, 2018)
Background: Teaching is a profession where teachers are exposed to use their voice excessively in many situations which impose the risk for developing morbidity caused to larynx, among them the most common is laryngitis. However, I felt that there was great need for educating primary school teachers on Prevention and Management of Laryngitis.Objectives: To find the effectiveness of Video Assisted Teaching Program (VATP) on Knowledge regarding Prevention and Management of Laryngitis among Primary School Teachers.Materials and methods: Quasi-experimental research design was adopted for the study with purposive sampling technique to select the sample (N=60) with n=30 in experimental group and control group of primary school teachers respectively. A structured knowledge questionnaire was used to assess the Knowledge; VATP was administered only to experimental group to find its effectiveness in comparison with control group. The findings of the study revealed deficit in knowledge of primary school teachers before administration of VATP.Results: The mean percentage knowledge score of post-test (79.80 %) was higher than the pretest (39.30%). The calculated paired 't' value is greater than the table value (0.05, 29df) = 2.045. It showed a significant difference between mean pre and post- test knowledge scores among experimental group. The mean percentage of knowledge scores in post-test (79.80%) among experimental group was higher than the post-test (39.80%) among control group. The 2 calculated unpaired 't' value is greater than the table value (0.05,58df) = 1.96. Calculated ÷ values showed significant association between post-test knowledge scores of respondents with their selected demographic variables.Conclusion: VATP was effective in increasing the knowledge of primary school teachers on Prevention and Management of Laryngitis.
Keywords: Effectiveness; VATP; Knowledge; Prevention; Laryngitis; Primary school teachers